Fine root decomposition and nutrient release of different age Caragana intermedia plantation in alpine sandy land - Li, Qingxue; Jia, Zhiqing; He, Lingxianzi; Zhao, Xuebin; Yang, Xiuben (Frontiers in Plant Science, 2025)
A better understanding of fine root decomposition and nutrient release characteristics is essential for accurate assessment and prediction of nutrient cycling in plantation ecosystems. Decomposition bag method was used to study the fine root (1 mm< D ≤ 2 mm, 0.5 mm< D ≤ 1 mm and D ≤ 0.5 mm) decomposition and nutrient release of Caragana intermedia plantation with different age (4-, 9-, 11-, 16- and 22-years old) in Gonghe Basin of the Tibetan Plateau. The results showed that (1) The C and K contents of fine root with 1 mm< D ≤ 2 mm and 0.5 mm< D ≤ 1 mm were higher than those D ≤ 0.5 mm. The N content of all fine root was significantly increased (P< 0.05), while the K content was significantly decreased (P< 0.05) with plantation age. (2) In the first decomposition period (81d), the fine root mass decomposition and nutrient release rate reached more than 50% (except P), and the K release was the fastest (76.86-94.73%). (3) The decomposition coefficient and nutrient release rate increased with fine root diameter. Only the fine root with 1 mm< D ≤ 2 mm decomposition rate decreased (except 9-year-old) with plantation age. (4) The mass loss and nutrient release of fine root were positively correlated with their K, C, N and P contents (P< 0.01). RDA analysis showed that the K content of fine root had the highest explanation for the mass loss and nutrient release (68.50-91.50%), followed by the C content (5.10-20.20%), and both reached a very significant level (P< 0.01).